Recreational and informative study benefits that adolescents receive by accessing the radio - Sitorus, Ferry Rhendra Pananda Putra (Jurnal Studi Komunikasi, 2023)
Adolescents desire to obtain information and news that can be fulfilled through various means and media, especially online media. Radio programmes are among the most popular media among teenagers in Jayapura City. Susanti and Wahyuni (2017) argue that radio is feasible to access, considering that it is a cheap and uncomplicated medium. This study aims to determine the adolescents' encouragement and benefits by accessing various programmes available on Swaranusa Bahagia (SNB) 1170 AM radio in Jayapura City. This study used a qualitative approach with an explanatory research type. There were 21 informants in this study consisting of 12 youth informants, six radio informants, and three Indonesian Broadcasting Commission informants. The study results stated that the youth were encouraged to access programmes on SNB 1170 AM radio in Jayapura City because of (1) information, (2) entertainment, (3) inspirational stories and words, and (4) friends. The findings and results of this research can be used by the radio in evaluating, revising, and developing its various broadcast programmes.